1993
DOI: 10.1007/bf00199619
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of abscisic acid in needles of Abies alba Mill. by electron capture gas chromatography

Abstract: Summary. The amount of abscisic acid (ABA) in needles of silver fir from a natural location was investigated with regard to position in the crown, damage, seasonal variation, and needle age. Because of problems of quantification of ABA in coniferous needles, which contain numerous secondary plant products, a method for reliable determination of both isomers cis-trans-ABA (c-ABA) and transtrans-ABA (t-ABA) was developed. By means of gas chromatography (GC) using an electron capture detector (ECD) and a programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In fact, in our preliminary experiments during which irrigation was stopped for 1 week, concentration of ABA in needles of 10-year-old P. densiflora seedlings exceeded 2,000 ng/g −1 DM, and WC of the needles decreased. However, Kraus and Ziegler (1993) showed that the maximum concentration in needles of silver fir (Abies alba) was achieved in May to June whereas the content was minimal in August/September. This results is similar to our results although they could not detect significant correlation between the amount of ABA and the needle age.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, in our preliminary experiments during which irrigation was stopped for 1 week, concentration of ABA in needles of 10-year-old P. densiflora seedlings exceeded 2,000 ng/g −1 DM, and WC of the needles decreased. However, Kraus and Ziegler (1993) showed that the maximum concentration in needles of silver fir (Abies alba) was achieved in May to June whereas the content was minimal in August/September. This results is similar to our results although they could not detect significant correlation between the amount of ABA and the needle age.…”
Section: Discussionmentioning
confidence: 96%
“…The possibility of a missing or inactive signalling pathway in the stomata of conifers leads to the final explanation for the contrast between the angiosperm and two conifer species: a fundamental difference in stomatal control by ABA between the two lineages. A limited number of studies have investigated ABA f in conifers using physicochemical methods ( Kraus and Ziegler, 1993 ; Hoffman et al , 1999 ; Kong et al , 2009 ). These studies all indicate that ABA f in conifers, including Pinaceae ( Kraus and Ziegler, 1993 ; Kong et al , 2009 ) and Taxaceae ( Hoffman et al , 1999 ) species, were typically >400 ng g −1 fresh weight under well-watered conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies have investigated ABA f in conifers using physicochemical methods ( Kraus and Ziegler, 1993 ; Hoffman et al , 1999 ; Kong et al , 2009 ). These studies all indicate that ABA f in conifers, including Pinaceae ( Kraus and Ziegler, 1993 ; Kong et al , 2009 ) and Taxaceae ( Hoffman et al , 1999 ) species, were typically >400 ng g −1 fresh weight under well-watered conditions. This is in contrast to angiosperm species under similar unstressed conditions for which ABA f is typically <100 ng g −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The third requirement relates to the speed of ABA synthesis over a timeframe that matches apparent ABA-driven stomatal responses. In terms of changing soil water deficit (over days), this condition is met in all vascular land plants ( Kraus and Ziegler, 1993;Hoffman et al, 1999;Kong et al, 2009;McAdam and Brodribb, 2013), but only in angiosperm does ABA synthesis appear to occur over a timeframe that corresponds to the dynamics of stomatal response to VPD .…”
Section: Co-option Of An Ancient and Highly Conserved Aba Signaling Pmentioning
confidence: 99%